(untitled) (Proximus Journal of Sports Science and Physical Education, 2024)
In this article, the author tried to shed light on the psychological features of feeling the gap in boxers through a new methodology. The author tried to explain the elements of feeling of distance in boxers using a device that allows measuring nine types of distance in boxers.